Application for Breaking Dormance and Giving Bokashi Salak Steel on the Growth of Salak (Salacca Sumatrana) Seeds - Eka, Eka nurwani ritonga (Talenta Publisher, 2021)
The purpose of this study was to determine the effect of breaking dormancy and giving bokashi bark leaves on the growth of salak ( Salacca Sumatrana ) seedlings. This study used a factorial randomized block design (RBD) with 3 blocks (replications). For the factor is the act of breaking dormancy and giving bokashi bark midrib. The statistical results showed that the treatment of dormancy breaking action had a significant effect, on the treatment of leaf area and plant height, the statistical results on the application of salak plant bokashi fertilizer did not show a significant effect on plant height and leaf area. Â